Counselling Psychology in Canada. Issue 2 (2nd April 2016) - Bedi, Robinder Paul; Sinacore, Ada; Christiani, Kayla D.
Abstract : Counselling psychology in Canada has experienced tremendous growth and greater recognition within the last 30 years. However, there is little empirical research on the practice of counselling psychology in Canada and the characteristics of Canadian counselling psychologists. We administered a 74 item questionnaire to 79 counselling psychologists who were members of the Counselling Psychology Section of the Canadian Psychological Association, achieving a 35.4% response rate. The survey asked various questions organized under the headings of: Background Information, Theoretical Orientations, Professional Activities, Training and Career Experiences, and Future. Overall, these Canadian counselling psychologists seem to see the discipline as moderately different from clinical psychology and from counsellor education, and are largely satisfied with their choice of career in counselling psychology. Results further indicate that independent practice is the most common work-setting and that respondents spend a large share of their time providing individual, non-career related, counselling/psychotherapy of primarily a rehabilitative/treatment-oriented nature. A strengths-focused approach was also highly valued by the sample. The development of the field, distinctive characteristics of Canadian counselling psychology, the place of counselling psychology in the Canadian health care delivery system, credentialing, professional organizations, education and training issues, allied professions, opportunities for the field, and threats to the field are also discussed.